2008
DOI: 10.1063/1.3021398
|View full text |Cite
|
Sign up to set email alerts
|

Finding stable α-quartz (0001) surface structures via simulations

Abstract: Reconstruction of α-quartz (0001) surfaces is studied using combined classical molecular dynamics and density functional theory. Five reconstruction patterns are identified, including three (2×1) patterns and two (1×1) patterns. The energetically most stable surface structure is found to be a (2×1) reconstruction pattern, and several patterns can coexist in a large-scale surface. A combination of structures can explain the experimentally observed (2×2) diffraction pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 18 publications
8
62
0
Order By: Relevance
“…The structure of the α-quartz bulk is known 34 and has also been calculated earlier. [35][36][37][38][39] To start with, we have optimized the α-quartz bulk structure using the ADF-BAND code with a couple of different E ex and compared results with those from the CASTEP calculations 25 , as well as with experimental values ( Table 1). The present PBE ADF-BAND data agree rather well with the PBE CASTEP ones 25 and with experimental values.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the α-quartz bulk is known 34 and has also been calculated earlier. [35][36][37][38][39] To start with, we have optimized the α-quartz bulk structure using the ADF-BAND code with a couple of different E ex and compared results with those from the CASTEP calculations 25 , as well as with experimental values ( Table 1). The present PBE ADF-BAND data agree rather well with the PBE CASTEP ones 25 and with experimental values.…”
Section: Resultsmentioning
confidence: 99%
“…20,30 In addition to 1 × 1 peaks, Steurer et al 21 also observed weak 2 × 2 peaks in helium diffraction experiments, which was assigned to alternating 2 × 1 patches. 27 Our simulations found that the 2 × 1 surface is more stable by 0.03 eV per surface SiO 2 group. Because the energy difference between the two surfaces is within the DFT error, we have studied both the 1 × 1 and 2 × 1 structures.…”
Section: Modelsmentioning
confidence: 91%
“…Several authors investigated numerically the chemisorption of atoms and molecules on freshly cleaved crystalline surfaces under high vacuum conditions. However, such cleaved surfaces are covered with highly reactive under‐coordinated atoms that either get immediately passivated under the ambient conditions or disappear as a result of surface reconstruction . As a result, the nature and the density of active sites on real disordered surfaces exposed to reactive fluxes may differ significantly from the predictions of ab‐initio calculation .…”
Section: Model Formulationmentioning
confidence: 99%